Step-by-Step Resumes : Build an Outstanding Resume in 10 Easy Steps!. - Salvador, Evelyn (JIST Publishing, 2010)
This revolutionary how-to workbook is the easiest way to create a winning resume no writing required! By filling in the blanks, checking the relevant boxes, and pasting in prewritten Resume Clip BulletsTM, readers can pull together an effective resume with ease. Also includes an exhaustive collection of thousands of powerful resume keywords to make your resume stand out in electronic databases. New for this edition is a section on integrating your resume into your social networking strategy, as well as new personal branding worksheets and expanded tips on e-mailing resumes.